Usagt study of creating model kits parts with the help of porous materials, including foundry waste - M. L. Kalinichenko; V. A. Kalinichenko; A. A. Andrushevich (Литьë и металлургия)
The paper considers current approaches to creating model kits parts for small-scale and individual production based on aluminum alloy waste. The aim of this study was to examine the prospects for using foundry waste of aluminum alloys and highly porous materials, in order to minimize the cost of manufacturing a model kit, as well as to develop recommendations for closing the pores of highly porous materials.